Analyzing the Consequences of Bad Outsourcing on Human Resources in Iranian Public Organizations - Pourezzat, Ali Asghar; ., Nader Seyed Kalali; ., Ghazaleh Taheri Attar (Information Management and Business Review, 2012)
The purpose of present research is to compare the status of perceptional and behavioral consequences on employees who serve in bad-outsourced departments of one of Iranian public organizations and the status of consequences on those employees who serve in non-outsourced departments of the same organization. In this line, such variables as organizational justice, organizational commitment, organizational identity, job security and anti-citizenship behaviors are compared between two groups of staff. The findings show that the rate of organizational justice, organizational commitment, organizational identity and job security among those employees who serve in bad-outsourced sectors is lower than similar variables among non-outsourced ones. In the meantime, there is no significant difference between groups in terms of anticitizenship behaviors variable. Noteworthy, present study was conducted in summer and fall 2010 in Iran.